Transformation of Scientific Interpretation in Indonesia: An Epistemological Criticism of the Scientific-Religious Paradigm in the Works of Purwanto and Mustofa - Firdarini; Tauhidah, Vieka; Said, Hasani Ahmad (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
The development of scientific interpretation (tafsīr ʿilmī) in Indonesia reflects an ongoing attempt to negotiate the relationship between Qur’anic revelation and modern scientific knowledge, while simultaneously raising epistemological questions concerning interpretive boundaries and methodological legitimacy. This study examines the transformation of scientific interpretation in the Indonesian context through a comparative analysis of the interpretive approaches of Agus Purwanto and Agus Mustofa, particularly in their engagement with kauniyyah verses. The primary objective of this research is to identify the dominant patterns of scientific interpretation employed by both figures and to assess their continuity with classical exegetical principles. Adopting a qualitative-descriptive design, this study employs comparative textual analysis supported by an evaluative framework derived from classical tafsīr theory, emphasizing linguistic accuracy, rhetorical coherence, and theological consistency as articulated by al-Zahabi. Primary data are drawn from the major works of Purwanto and Mustofa and are contextualized through relevant classical and contemporary literature on scientific exegesis. The findings demonstrate that Purwanto advances a revelation-based, scientific-textual model in which modern science functions as an explanatory tool subordinate to the Qur’anic text. In contrast, Mustofa represents a rational-speculative approach that positions contemporary scientific theories as the primary interpretive lens for metaphysical Qur’anic concepts. This study contributes to Qur’anic studies by offering an epistemological mapping of scientific interpretation in Indonesia and by advancing a critical framework for integrating scientific reasoning with textual fidelity and theological integrity in contemporary exegesis.